2018
DOI: 10.1371/journal.pone.0193210
|View full text |Cite|
|
Sign up to set email alerts
|

Microsomal prostaglandin E synthase-1 gene deletion impairs neuro-immune circuitry of the cholinergic anti-inflammatory pathway in endotoxaemic mouse spleen

Abstract: The cholinergic anti-inflammatory pathway (CAP) is an innate neural reflex where parasympathetic and sympathetic nerves work jointly to control inflammation. Activation of CAP by vagus nerve stimulation (VNS) has paved way for novel therapeutic strategies in treating inflammatory diseases. Recently, we discovered that VNS mediated splenic acetylcholine (ACh) release and subsequent immunosuppression in response to LPS associated inflammation is impaired in mice lacking microsomal prostaglandin E synthase-1 (mPG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…Also, it is known that the stimulation of the vagus nerve promotes the synthesis of ACh through a mechanism involving T cells, which act as a non-neural source of this neurotransmitter 31 . Similar to our results, a previous study has demonstrated the relationship between the release of this ACh and mPGES-1-dependent PGE 2 production in neuroimmune vagal activity 32 . However, findings in the literature are controversial.…”
Section: Discussionsupporting
confidence: 93%
“…Also, it is known that the stimulation of the vagus nerve promotes the synthesis of ACh through a mechanism involving T cells, which act as a non-neural source of this neurotransmitter 31 . Similar to our results, a previous study has demonstrated the relationship between the release of this ACh and mPGES-1-dependent PGE 2 production in neuroimmune vagal activity 32 . However, findings in the literature are controversial.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, the cholinergic anti-inflammatory pathway between the vagus nerve and the splenic nerve can allow the rapid and precise control of systemic cytokine production and the trafficking of inflammatory cells to distant sites (15,120). In more detail, microsomal prostaglandin E synthase-1 gene and PGE2 in the spleen have a crucial role in bridging the immune and nervous systems influenced by nicotine in vitro (121).…”
Section: Anti-inflammatory Effect Of Nicotine On Sepsis and Endotoxemiamentioning
confidence: 99%
“…Several studies have shown that PGE2 was a vital regulator for the function of vagus nerve system, 41 and mPGES-1 knockout mice showed the deficiency of ACh release. 42 Here, we show that PGE2 secretion from MSCs play the important role for ACh release, and when PGES-2/PTGES are inhibited, MSCs exhibit decreased abilities to promote ACh production and inhibit inflammatory cytokine expression, highlighting its role in CAP activation. Moreover, Suenaga A reported that intracellular cAMP levels were increased via the PGE2 receptors EP2 and EP4 and could increase the mRNA expression and activity of ChAT.…”
Section: Discussionmentioning
confidence: 68%